Geek Girls : Inequality and Opportunity in Silicon Valley - Twine, France Winddance, 1960- (Book collections on Project MUSE., 2022)
"Can girls code? Is "computer geek" synonymous with "white male"? Why do men greatly outnumber women at places like Google? Is the best way to deal with gender discrimination to 'lean in?' Much has been written about the tech industry's difficulties in addressing gender and racial concerns about bias and discrimination, yet rarely have we gotten a look inside this industry. In Geek Girls, France Winddance Twine focuses on first-hand accounts of these issues in the tech world. The book draws on over 100 interviews with male and female tech workers of diverse racial, ethnic, and educational backgrounds who are currently employed at tech firms such as Apple, Google, 4Square, and Twitter or at various start-ups in the San Francisco Bay area. Twine finds that many potential tech employees from privileged backgrounds have social networks-friendship ties, former classmates, neighbors, relatives--that they rely on to get priority in hiring and in gaining access to jobs in the tech industry. As a consequence of these practices, she argues, those who do not share either racial, cultural, or class backgrounds as well as educational affiliations of current tech company employees are not given the opportunity to compete. While there may not be overt racism or sexism in the tech industry it is clear that there are forms of residential and educational segregation at work as well as recruitment and cultural practices that marginalize women and non-Asian minorities. Importantly, virtually all tech firms espouse opposition to discrimination in the workplace, yet the author argues that workers describe routine practices that embrace just that kind of supposedly "outlawed" thinking. In this way, the culture of gender-blindness and color-blindness makes it difficult for individuals to name the forms of discrimination and or micro-aggressions that they are experiencing. Ultimately, the author suggests that these patterns can be changed and offers concrete insight into how the tech industry might go about putting these policies into place"--